Data-driven exploration of weak coordination microenvironment in solid-state electrolyte for safe and energy-dense batteries - Zhoujie Lao; Kehao Tao; Xiao Xiao; Haotian Qu; Xinru Wu; Zhiyuan Han; Runhua Gao; Jian Wang; Xian Wu; An Chen; Lei Shi; Chengshuai Chang; et al. (Nature Communications)
Abstract The unsatisfactory ionic conductivity of solid polymer electrolytes hinders their practical use as substitutes for liquid electrolytes to address safety concerns. Although various plasticizers have been introduced to improve lithium-ion conduction kinetics, the lack of microenvironment understanding impedes the rational design of high-performance polymer electrolytes. Here, we design a class of Hofmann complexes that offer continuous two-dimensional lithium-ion conduction channels with functional ligands, creating highly conductive electrolytes. Assisting with unsupervised learning, we use Climbing Image-Nudged Elastic Band simulations to screen lithium-ion conductors and screen out five potential candidates that elucidate the impact of lithium coordination environment on conduction behavior. By adjusting the covalency competition between Metal−O and Li−O bonds within Hofmann complexes, we can manipulate weak coordination environment of lithium-ion for rapid conduction kinetics. Li | |sulfurized polyacrylonitrile (SPAN) cell using solid-state polymer electrolytes with predicted Co(dimethylformamide)2Ni(CN)4 delivers an initial discharge capacity of 1264 mAh g−1 with a capacity retention of 65% after 500 cycles at 0.2 C (335 mA g−1), at 30 °C ± 3 °C. The assembled 0.6 Ah Li | |SPAN pouch cell delivers an areal discharge capacity of 3.8 mAh cm−2 at the second cycle with a solid electrolyte areal mass loading of 18.6 mg cm−2 (mass-to-capacity ratio of 4.9).